Design of Quantizers with Huffman Coding for Laplacian Source - Dincic, M.; Peric, Z. (Elektronika ir Elektrotechnika, 2010)
Two new types of hybrid quantizers are proposed for low and moderate bit-rates. They are compared with the uniform and the nonuniform quantizers in two cases: when VLC (variable length code) is not used and when Huffman VLC is used. It is shown that our hybrid quantizers have excellent performances.